Increasing kailan profits using smart farming in the form of a digital water timer - Syafri, Zelin Relavebrian; Tinaprilla, Netti; Rifin, Amzul (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: Agriculture is no longer facing challenges in the classic way but with modern method called smart farming. Hope this can be a solution to improve agricultural quality and productivity which will lead to increased farming profits. One of them is digital water timer, it helps distributing water in hydroponics. In reality, not many farmers implemented smart farming or greenhouses due to lack of information and costs. This study aims to analysis profit and the factors influencing it. Methods: The research was conducted in Jambi City collected with the help of questionnaires and literature study. Primary data was collected from 155 respondents including hydroponics with smart farming in greenhouses, hydroponics non-smart farming in greenhouses, hydroponics only, and conventional farming. The analytical research method used is quantitative descriptive and data processing using the R/C ratio formula, whereas to determine the factors using multiple linear regression with F-test and t-test. Results: The results showed that the R/C ratio is 1.74, which means farming is profitable to implement. Hydroponics with smart farming provides the highest profit among other technologies and costs less than non-smart farming. The profit obtained is 18.6% higher than non-smart farming. The higher the technology, the more production will increase. Smart farming affects positively to the Kailan production followed by other factors that is land area. Conclusion: This finding provides technology such as smart farming has potential impacts to improve farm profit.